Network pharmacology and molecular docking reveals the therapeutic mechanism of Musa acuminata against obsessive-compulsive disorder - Hasan Ansari, Prekshi Garg, Rashmi K. S, Grisilda Vidya Bernhardt, Prachi Srivastava (Journal of Applied Pharmaceutical Science, 2024)
Network pharmacology integrates systems biology and bioinformatics to explore the intricate relationships among drugs, targets, diseases, and other molecular docking used to explore the effect of Musa acuminata against obsessive-compulsive disorder (OCD). OCD is a behavioral and mental neurological condition. The occurrence of patients with OCD has increased in recent times due to both genetic and environmental factors. Genetic factors involve variations in certain genes that give instructions for proteins that react to or transport the neurotransmitter known as serotonin which has been associated with an increased risk of OCD. Thus, the present study aims to establish the therapeutic properties of M. acuminata, that is, banana against environment-induced OCD. The active components of M. acuminata were screened through IMPPAT 2.0, NPASS, and HMDB databases. Corresponding gene targets of active ingredients were found by using STITCH and comparative toxicogenomics database databases. Similarly, the genes involved in OCD were screened with the help of the Gene Cards and DisGeNET database. Utilizing the Gene Cards and DisGeNET database, 2,966 gene targets of OCD were obtained. The network interaction map of gene targets was created using STRING and the CytoHubba plugin of Cytoscape, and the top interacting targets were then filtered away. Finally, the prophylactic activity of active ingredients of M. acuminata against OCD was studied through a molecular docking strategy. This research utilized a network pharmacology-integrated molecular docking approach to study the therapeutic properties of M. acuminata against OCD.
Keywords: Musa acuminata, obsessive-compulsive disorder, OCD, network pharmacology, molecular docking